Stimulation of regulatory dendritic cells suppresses cytotoxic T cell function and alleviates DEN-induced liver injury, fibrosis and hepatocellular carcinoma - Wang, Junjie; Gong, Pixu; Liu, Qingqing; Wang, Menglei; Wu, Dengfang; Li, Mengyu; Zheng, Shujie; Wang, Han; Long, Qiaoming (Frontiers in Immunology, 2025)
BackgroundDendritic cells (DCs) are versatile professional antigen-presenting cells and play an instrumental role in the generation of antigen-specific T-cell responses. Modulation of DC function holds promise as an effective strategy to improve anti-tumor immunotherapy efficacy and enhance self-antigen tolerance in autoimmune diseases.MethodsWild-type (WT) and TLR2 knockout (KO) mice at 2 weeks of age were injected intraperitoneally (i.p.) with a single dose of diethylnitrosamine (DEN) to induce hepatocellular carcinoma (HCC). Four weeks later, WT and KO mice were randomly divided into control and treatment groups and treated once every two days for 30 weeks with phosphate buffered saline (PBS) and a mix of 4 TLR2-activating lactic acid-producing probiotics (LAP), respectively. Mice were euthanized after 30 weeks of LAP treatment and their liver tissues were collected for gene expression, histological, flow cytometric and single-cell RNA sequencing analyses.ResultsWe demonstrate here that oral administration of a mix of TLR2-activating LAP triggers a marked accumulation of regulatory DCs (rDCs) in the liver of mice. LAP-treated mice are protected from DEN-induced liver injury, fibrosis and HCC in a TLR2-dependent manner. Single-cell transcriptome profiling revealed that LAP treatment determines an immunosuppressive hepatic T-cell program that is characterized by a significantly reduced cytotoxic activity. The observed functional changes of T cells correlated well with the presence of a hepatic DC subset displaying a regulatory or tolerogenic transcriptional signature.ConclusionOverall, these data suggest that stimulation of regulatory dendritic cells (rDCs) in the liver by LAP suppresses cytotoxic T-cell function and alleviates DEN-induced liver damage, fibrosis and tumorigenesis.